WAGES: A SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Rahma, Deshinta Raisa; Sopiah, Sopiah (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2024)
This research aims to explore the topic of a wage. The literature analyzes from 31 articles from two database Taylor & Francis and Scopus which taken from Publish or Perish during the period 2017-2022, analyze with bibliometric and screening using PRISMA method to gain 31 articles. The outcome of the review indicated 127 authors from co-authorship data, four new keywords overlay from co-occurrence (employment, automation, job stress, and corporate innovation). The top 3 citations narrate about gender wage gap, minimum wage, and wage policy. This literature review can be used for a guidance for the next researcher regarding labor wage and the connection with other keywords that appropriate.